Prediction of Residual Disease After Primary Cytoreductive Surgery for Advanced-Stage Ovarian Cancer: Accuracy of Clinical Judgment. Issue 9 (1st November 2009) - Gerestein, Cornelis G.; van der Spek, Dirkina W.; Eijkemans, Marinus J.; Bakker, Jeanette; Kooi, Geertruida S.; Burger, Curt W.
Abstract : Objectives: Treatment of patients with an advanced-stage epithelial ovarian cancer (EOC) is based on cytoreductive surgery and platinum-based chemotherapy. Amount of residual disease after primary cytoreductive surgery is an important prognostic factor. The objectives of the present study were to evaluate the accuracy and reproducibility of preoperative clinical judgment of residual disease after primary cytoreductive surgery and to compare the predictive performance of the offhand assessment to the predictive performance of prediction models. Materials and Methods: Fifteen observers (5 gynecologic oncologists, 5 gynecologists, and 5 senior residents) were offered preoperative data of 20 patients with advanced-stage EOC who underwent primary cytoreductive surgery. The observers were asked to predict residual disease after cytoreductive surgery (≤1 or >1 cm). Their estimation was compared with the performance of 2 prediction models. Results: Overall, suboptimal cytoreduction was predicted with a sensitivity of 50% and a specificity of 56%. The intraclass correlation coefficient was 0.27. χ 2 test showed no significant difference in prediction of suboptimal cytoreduction between the different subgroups and prediction models. Conclusions: Clinical judgment of residual disease after primary cytoreductive surgery in patients with advanced-stage EOC shows limited accuracy. Given the poor interobserver reproducibility, prediction models could attribute to uniform treatment decisions and improve counseling.